Melatonergic drugs in development - Carocci A; Catalano A; Sinicropi MS (Dove Medical Press, 2014)
Alessia Carocci,1 Alessia Catalano,1 Maria Stefania Sinicropi2 1Department of Pharmacy–Drug Sciences, University of Bari Aldo Moro, Bari, 2Department of Pharmacy, Health and Nutritional Sciences, University of Calabria, Cosenza, Italy Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is widely known as "the darkness hormone". It is a major chronobiological regulator involved in circadian phasing and sleep-wake cycle in humans. Numerous other functions, including cyto/neuroprotection, immune modulation, and energy metabolism have been ascribed to melatonin. A variety of studies have revealed a role for melatonin and its receptors in different pathophysiological conditions. However, the suitability of melatonin as a drug is limited because of its short half-life, poor oral bioavailability, and ubiquitous action. Due to the therapeutic potential of melatonin in a wide variety of clinical conditions, the development of new agents able to interact selectively with melatonin receptors has become an area of great interest during the last decade. Therefore, the field of melatonergic receptor agonists comprises a great number of structurally different chemical entities, which range from indolic to nonindolic compounds. Melatonergic agonists are suitable for sleep disturbances, neuropsychiatric disorders related to circadian dysphasing, and metabolic diseases associated with insulin resistance. The results of preclinical studies on animal models show that melatonin receptor agonists can be considered promising agents for the treatment of central nervous system-related pathologies. An overview of recent advances in the field of investigational melatonergic drugs will be presented in this review. Keywords: MT1/MT2 ligands, circadian rhythms, melatonin